2000
DOI: 10.1021/bi992553w
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Orotidine 5‘-Monophosphate Decarboxylase:  Catalysis by Destabilization of the Substrate

Abstract: The mechanism of orotidine 5'-monophosphate decarboxylase (OMP decarboxylase, ODCase) was studied using the decarboxylation of orotic acid analogues as a model system. The rate of decarboxylation of 1,3-dimethylorotic acid and its analogues as well as the stability of their corresponding carbanion intermediates was determined. The results have shown that the stability of the carbanion intermediate is not a critical factor in the rate of decarboxylation. On the other hand, the reaction rate is largely dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
75
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 28 publications
7
75
0
Order By: Relevance
“…1,7 Studies on the gas-phase stability of the corresponding carbanions 3, 8, and 9 have established a lack of correlation between the rate of decarboxylation and the gas-phase stability of resulted carbanions. 7 It was found that carbanion 3 is much more stable while carbanions 8 and 9 share the same stability. 6,7 As a result, a two-step mechanism has been proposed to account for the large difference in rate constants measured for acids 1, 4, and 5 (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,7 Studies on the gas-phase stability of the corresponding carbanions 3, 8, and 9 have established a lack of correlation between the rate of decarboxylation and the gas-phase stability of resulted carbanions. 7 It was found that carbanion 3 is much more stable while carbanions 8 and 9 share the same stability. 6,7 As a result, a two-step mechanism has been proposed to account for the large difference in rate constants measured for acids 1, 4, and 5 (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Most of the studies involve the investigation of the nature and stability of the intermediate. As shown in Scheme 1, acid 1 decarboxylates at elevated temperatures to give 1,3-dimethyluracil (2) as the sole product.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations